DEMOCRATIC AND AUTOCRATIC STRATEGIES: TEACHING ENGLISH AT NURSING CLASS - Sitti Maryam Hamid; Slamet Setiawan (Universitas Muhammadiyah Makassar, 2019)
Teaching English for Specific Purposes (ESP) is familiar one in the field of English Language Teaching (ELT). Unfortunately, in practice, many teachers still teach English using the same methods for different departments. Hence, this study aims to look into teachers’ strategies in teaching English at Nursing Class and students’ responds through those teaching strategies. Data were collected from two teachers and 30 students of SMK Yapika Makassar (private vocational school in Makassar, South Sulawesi). To analyse, teachers’ strategies and student’s responds were classified into observation, questionnaire, and interviews. There were two strategies that applied in this study namely democratic (group discussion, student presentation) and autocratic strategies (lecture method and multimedia method). Finding presents frequency of group discussion dominant used by teachers than other strategies. Besides, it related to student’s responds through teaching strategies. Therefore, students prefer democratic strategies than autocratic strategies.